Method of Fairy-tale Analysis in the Study of Ethnic Identity - Odintsova, Anastasiia (East European Journal of Psycholinguistics, 2015)
The article presents the results of the ethnic identity research by method of fairy-tale analysis. It deals with the particular characteristics and factors of the phenomenon of ethnic identity, characterized by awareness of belonging to a certain ethnic group. The effectiveness of the appliance of methods of fairy-tale therapy and in particular fairy-tale analysis in the ethnic identity research has been proved theoretically and empirically. The phenomenon of ethnic identity in article is examined by the nature of relationship between the images of the selfishness of the person under investigation and the image of the country in which he/she resides, described in the author’s fairy-tale. To achieve the objective of the research, a special instruction was created for writing a fairy-tale by the interviewed about meeting of two characters – the image of selfishness and Ukraine. The developed algorithm of fairy-tale story analysis is given and described in the main part of the article. The results of empirical research, which was attended by students aged 18 to 20 years, have been presented. The analysis of the research results made it possible to distinguish the most typical images of Ukraine, namely the image of kalyna (arrowwood) and rushnyk (towel), and unique original images – willow, sunflower, wind. The symbolism of the stated images in folklore and folk traditions has been analysed. The varieties of attitude to these images of interviewed, namely establishing friendly relations, desire to protect and help, have been defined. This article provides an example of the fairy-tale material analysis by author’s algorithm. The scientific novelty of the paper is that the narrative analysis, namely method of fairy-tale analysis with the purpose of ethnic identity research has been used at the empirical level for the first time. The obtained results can be used for further psycholinguistic researches, development of diagnostic and therapeutic instrumentarium.ReferencesBerger, P., Luckmann, T. (1995). Social’noe konstruirovanie real’nosti. Traktat posociologii znanija [The social Construction of Reality. A Treatise on the Sociology of Knowledge].Moscow: Medium.Cooley, Ch. (1994). Socіal’na samіst’ [The Social Self]. Moscow: Moscow StateUniversity.Erikson, E. (2006). Identichnost’. Junost’ i krizis [Identity. Yunost and Crisis].Moscow: Progress.Freud, S. (1991). Massovaja psihologija i analiz chelovecheskogo "Ya" [MassPsychology and the Analysis of the "I"]. Tbilisi: Merani.James, W. (2000). Vvedenie v Filosofiju [Introduction to Philosophy]. Moscow:Respublika.Jung, K. (2001). Arkhetip i Simvol [Archetype and Symbol]. Moscow: AkademicheskiyProekt.Maslow, A. (1967). A theory of metamotivation: the biological rooting of the valuelife. Humanistic Psychology, 7, 93 – 127.Mead, G. (2000). Duh, Samist’ i Suspil’stvo. Z Tochky Zoru Social’nogo Biheviorysta[The Spirit, Self and Society. In Terms of Social Behaviorist]. Kyiv: Ukrai’ns’kyj Centr Duhovnoi’Kul’tury.Muhlynkina, Ju. (2011). Jetnicheskaja identichnost’: sushhnost’, soderzhanie iosnovnye tendencii razvitija [Ethnic identity: the nature, content and development trends].Moscow: Labirint.Rogers, N. (1990). Tvorchestvo kak usilenie sebia [The creativity as strengtheningitself]. Voprosy Psihologii, 1, 164–168.Tajfel, H. (1982). Social’naja identichnost’ i mezhgruppovye otnoshenija [The socialidentity and intergroup relations]. Moscow: Labirint.Zasyekina, L. (2014). Ukrainski pryslivia i prykazky yak psyholingvistychnyi resurskognityvno-povedinkovoyi terapii tryvozhnyh rozladiv [Ukrainian proverbs and sayings aspsycholinguistic resource of cognitive and behavioral therapy of anxiety disorders]. PsychologicalProspects, 24, 112–124.